INITIAL CHALLENGES IN LEARNING LANGUAGE AND OVERCOME THESE ISSUES WITH EFFECTIVE TEACHING STRATEGIES - Rayimaliyeva Yoqutxon Zohidjon qizi; Zakirova Diyora Shavkat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explains difficulties of learning English as a second language and overcome these abstacles with intensive teaching methods .Each method is characterized with examples and meanings to illustrate effective teaching approaches in creating interactive classroom atmosphere. Overall,speacial attention is paid to teaching English to non – native speakers effectively,emphasizing the importance of overcoming language learning difficulties.